The Cartographic representation of fruit tree production variation in Iraq using geographic information systems (GIs) (Journal of the College of Basic Education, 2022)
The research aims to use the cartographic representation method to show the spatial variation of fruit trees in Iraq. The research relied on the analytical method, which is represented by analyzing the (numerical) statistical tables of fruit trees using a geographic information system (GIS) program. The research showed the presence of spatial variation in winter fruit trees. And summer in terms of the numbers, types, productivity and productivity of one tree at the level of the governorates of Iraq for the 2018-2019 agricultural season, especially after the return of agricultural production to the provinces that were under the control of ISIS terrorist, and the research showed the existence of spatial variation in the areas where these crops were produced as the governorates were occupied (Salah Religion, Diyala, Wasit, and Baghdad) the first ranks in the production of fruit trees, while the governorates of (Najaf, Qadisiyah, Babel and Kirkuk) recorded the least productive governorates, and this discrepancy was represented in the form of quantitative distribution maps and in various methods to give the reader a clear visual image instead of the statistical tables represented by digital data. Research with a set of recommendations, the most important of which is to support and encourage the provinces that occupied the advanced ranks in the production and the possibility of relying on them to meet the local demand, as well as encouraging agricultural specialization in those areas and other recommendations